2010
DOI: 10.1074/jbc.m109.077339
|View full text |Cite
|
Sign up to set email alerts
|

Photox, a Novel Actin-targeting Mono-ADP-ribosyltransferase from Photorhabdus luminescens

Abstract: Photorhabdus luminescens is a pathogenic bacterium that produces many toxic proteins. The mono-ADP-ribosyltransferases (mARTs) are an enzyme class produced by numerous pathogenic bacteria and participate in disease in plants and animals, including humans. Herein we report a novel mART from P. luminescens called Photox. This 46-kDa toxin shows high homology to other actin-targeting mARTs in hallmark catalytic regions and a similar core catalytic fold. Furthermore, Photox shows in vivo cytotoxic activity against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 50 publications
0
42
2
Order By: Relevance
“…(31). Effective inhibitors of mART (ExoA c ) activity can be screened in this yeast-based system, where such agents abrogate the growth defect phenotype (33). The yeast strains employed for initial screening were W303 (wild type), ERG6 Ϫ (which lacks the ⌬24-sterol C-methyltransferase), MTID:2955 (which lacks two master regulators in the expression of pleiotropic drug response elements), and 2775 and 7034 (deficient in mannosylphosphate transferase); however, no differences between the various yeast strains were observed, and so W303 was used as the tester strain for this study (3).…”
Section: Resultsmentioning
confidence: 99%
“…(31). Effective inhibitors of mART (ExoA c ) activity can be screened in this yeast-based system, where such agents abrogate the growth defect phenotype (33). The yeast strains employed for initial screening were W303 (wild type), ERG6 Ϫ (which lacks the ⌬24-sterol C-methyltransferase), MTID:2955 (which lacks two master regulators in the expression of pleiotropic drug response elements), and 2775 and 7034 (deficient in mannosylphosphate transferase); however, no differences between the various yeast strains were observed, and so W303 was used as the tester strain for this study (3).…”
Section: Resultsmentioning
confidence: 99%
“…Activity assays were performed following a slightly modified protocol as described previously (30). In brief, appropriate concentrations of VahC (62 nM) or VahC mutants (0.22-3.3 M) were mixed with varying concentrations of ⑀-NAD ϩ or chicken skeletal actin (50 and 35 M for saturating concentrations, respectively), and fluorescence emission was monitored in a stopped-flow spectrometer, model SX20-MV (Applied Photophysics, Leatherhead, UK) as the reaction progressed at 25°C (295-nm excitation, 395-nm emission cut-off filter).…”
Section: CMmentioning
confidence: 99%
“…The k cat value of actin for the actin-targeting toxins Photox and iota was relatively high, whereas for SpyA, the actin k cat was significantly lower (41,61). The greater SpyA k cat value for vimentin indicated that vimentin was a more highly modified substrate than actin.…”
Section: Discussionmentioning
confidence: 94%
“…ADPRT activity against vimentin and actin was determined using the ⑀-NAD ϩ fluorescence assay (41). The release of nicotinamide during catalysis abolished the intrinsic fluorescent quenching, leading to an increase in fluorescence, and was used as a proxy to measure the formation of ADP-ribosylated vimentin and actin.…”
Section: Resultsmentioning
confidence: 99%